The effect of different strength training programs on young athletes` sprint performance - Dasteridis, G.; Pilianidis, T.; Mantzouranis, N. (Studies in Physical Culture and Tourism, 2011)
The aim of this study was to investigate the effect of strength training on sprinting performance. 27 young male athletes were divided into three groups: neuro-muscular (NGroup), hypertrophy (HGroup) and control (CGroup). The athletes in NGroup and HGroup were training 3 times per week for 8 weeks. The fastest times of 30 m and 60 m testing trials were recorded prior to, in the middle of and at the end of the training program. ANOVA revealed a significant improvement in fastest times in both 30 m (8%) and 60 m (5.9%) runs in the athletes from the NGroup. Similarly, the improvement in speed of HGroup athletes was 6.2% in 30 m and 5.2% in 60 m, respectively, while a slight improvement in fastest times in 30 m (2.1%) and 60 m (2.4%) was shown in the CGroup athletes. Conclusively, a greater improvement in speed in both 30 m and 60 m was observed in the athletes from the NGroup.